First demonstration experiment of the neutron rotation method for detecting nuclear material. (1st September 2021) - Komeda, M.; Toh, Y.; Tanabe, K.; Kitamura, Y.; Misawa, T.
Highlights: The first demonstration experiment of the neutron rotation method was performed. The fundamental principle of the new method was presented. We developed the rotation device that the angular speed of the disk is 3000 rpm. The new device has characteristics of portability and low cost. Abstract: The rotation method is a novel method for detecting nuclear materials using a neutron source such as californium. In this method, while a neutron source is rotated rapidly nearby a measurement object, neutron measurement is carried out by synchronizing the rotation motion. If the object contains a nuclear material, as the rotation speed increases, the larger deformation of time distribution of neutron counts is observed, which in turn resulted to the detection of the nuclear material. In addition to its features of low cost and portability, this method is capable of detecting uranium that emits very few spontaneous fission neutrons. This study presents the fundamental principle of this method and its effectiveness for detecting nuclear materials through the experimental verifications.